Efektivitas Program Peningkatan Kompetensi Sumber Daya Aparatur di Komisi Pemilihan Umum Kota Medan - Simamora, Benny Estrada; Batubara, Beby Masitho; Kurniaty, Evy Yunita (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
This study evaluates the effectiveness of capacity-building programs for civil servants within the Regional Election Commission (KPU) of Medan City, by the State Civil Apparatus Law. Employing a qualitative descriptive approach, data was collected through observation, interviews, and documentation. The findings indicate that the effectiveness of the program relies on the leadership of the KPU in overseeing election regulations and schedules. Effective performance is influenced by a robust leadership system. KPU commissioners ensure that election schedules are aligned with KPU regulations. These findings are based on the Budiani program effectiveness indicators: target accuracy, socialization, objectives, and monitoring. Enhancing civil servant competencies is a crucial aspect for improving KPU performance. This research contributes to understanding the factors influencing the effectiveness of capacity-building programs within local government environments.